Low-back pain patients learn to adapt motor behavior with adverse secondary consequences - Dieën, Jaap van; Flor, Herta; Hodges, Paul (Exercise and sport sciences reviews, 2017)
We hypothesize that changes in motor behavior in individuals with low-back pain are adaptations aimed at minimizing the real or perceived risk of further pain. Through reinforcement learning, pain and subsequent adaptations result in less dynamic motor behavior, leading to increased loading and impoverished sensory feedback, which contribute to cortical reorganization and proprioceptive impairments that reduce the ability to control lumbar movement in a robust manner.
Gesehen am 07.09.2018